Stomatal properties of Arabidopsis cauline and rice flag leaves and their contributions to seed production and grain yield. (15th December 2022) - Ding, Ming; Zhu, Yiyong; Kinoshita, Toshinori
Abstract: Cauline leaves on the inflorescence stem of Arabidopsis thaliana may play important roles in supplying photosynthetic products to sinks, such as floral organs. Flag leaves in rice ( Oryza sativa ) have a higher photosynthetic capacity than other leaves, and are crucial for increasing grain yield. However, the detailed properties of stomata in cauline and flag leaves have not been investigated. In Arabidopsis, stomatal conductance and CO2 assimilation rate were higher in cauline leaves under white light than in rosette leaves, consistent with higher levels of plasma membrane (PM) H + -ATPase, a key enzyme for stomatal opening, in guard cells. Moreover, removal of cauline leaves significantly reduced the shoot biomass by approximately 20% and seed production by approximately 46%. In rice, higher stomatal density, stomatal conductance, and CO2 assimilation rate were observed in flag leaves than in fully expanded second leaves. Removal of the flag leaves significantly reduced grain yield by approximately 49%. Taken together, these results show that cauline and flag leaves have important roles in seed production and grain yield through enhanced stomatal conductance and CO2 assimilation rate. Abstract : Arabidopsis cauline leaves and rice flag leaves have important roles in seed production and grain yield, through enhanced stomatal conductance and CO2 assimilation rate caused by increased plasma membrane H + -ATPase activity.